Chinese Food Culture in Pakistan: Analysis of Chinese Food Culture within the Framework of the CPEC Project - Muhammad Asif; Abdoulaye M’Begniga; Majid Ali; Muhammad Usman (PT FORMOSA CENDEKIA GLOBAL, 2022)
In philosophy, “culture” denotes something separate from nature. Sociology, like ethology, defines culture as